Exploring the Affordable Housing Solutions for the Resettlement Projects of Padma Bridge - Rashid, Masud Ur; Islam, Syed Monirul; Amin, Abdullah Al (Global Journal of Cultural Studies, 2023)
The construction of Padma Bridge in Bangladesh has necessitated the resettlement of displaced residents, highlighting the need for affordable and sustainable housing solutions aligned with Sustainable Development Goals 9 (Industry, Innovation, and Infrastructure), 10 (Reduce inequality), and 11 (Sustainable Cities and Communities). This study aims to engage undergraduate architecture students in a design studio exercise to develop innovative housing models for resettlement projects, addressing displaced communities' social, economic, and environmental challenges. A multi-criteria decision analysis (MCDA) framework is introduced, integrating stakeholder data. In the design studio, students explore housing alternatives and concentrate on community-driven cooperative housing, assessing their effectiveness, feasibility, and sustainability using the MCDA framework. The exercise produces a range of housing solutions that balance affordability, sustainability, and community-centric design. Students demonstrate the potential of novel approaches to address the complex challenges displaced communities face and contribute to equitable development in Bangladesh. Engaging architecture students in developing affordable housing solutions provides valuable insights for policymakers and stakeholders in resettlement. The study emphasizes the need for holistic, participatory approaches and highlights the role of innovative, sustainable housing models in enhancing the quality of life for those affected by the Padma Bridge project, aligning with the SDGs.